Fabrication and Characterisation of Aligned Discontinuous Carbon Fibre Reinforced Thermoplastics as Feedstock Material for Fused Filament Fabrication - Blok, Lourens Gerrit (Materials (Basel), 2020)
In this work, aligned discontinuous fibre composite (ADFRC) tapes were developed and investigated as precursors for a novel 3D printing filament. ADFRCs have the potential to achieve mechanical performance comparable to continuous fibre reinforced composites, given sufficient fibre length and high level of alignment, and avoid many of the manufacturing difficulties associated with continuous fibres, e.g., wrinkling, bridging and corner radii constraints. Their potential use for fused filament fabrication (FFF) techniques was investigated here. An extensive down-selection process of thermoplastic matrices was performed, as matrix properties significantly impact both the processing and performance of the filament. This resulted in four candidate polymers (ABS, PLA, Nylon, PETG) which were used to manufacture ADFRC tapes with a V(f) of 12.5% using the high performance discontinuous fibre (HiPerDiF) technology and an in-house developed continuous consolidation module. Tensile stiffness and strength up to 30 GPa and 400 MPa respectively were recorded, showing that a discontinuous fibre filament has the potential to compete with continuous fibre filaments.